POWER OUTPUT DIFFERENCES IN THE CONTEXT OF DYNAMIC STRETCHING IN YOUNG MALE ATHLETES - GHERȚOIU, Dan Mihai; MOCA, Cosmin Mihai (Studia Universitatis Babeş-Bolyai Educatio Artis Gymnasticae, 2021)
Introduction. Static stretching is generally performed in sport and clinical settings, although dynamic stretching is increasingly being used before exercise and competition. There is strong evidence that a decrease in muscle strength can be the result of longer durations of static stretching, a phenomenon called stretching-induced force deficit. Objectives. The aim of this paper was to determine the jumping power output differences before and after dynamic stretching in young male athletes. Materials and Methods. The participants in this study were young male athletes (N = 18), aged from 14 to 16 years old that underwent two measurements on the MGM-15 carpet. Results. There was a significant statistical difference in the scores between the control and after dynamic stretching conditions. This means that the dynamic stretching had an influence over the power output of the subjects. Conclusion. The results revealed that the power output was significantly improved (increased) after dynamic stretching compared to control measurement. Furthermore, dynamic stretching should be performed in order to increase the power output performances of jumping. REZUMAT. Diferențele de putere în contextul stretchingului dinamic la tinerii sportivi. Introducere. Stretchingul static este folosit de obicei în activități sportive și în recuperare dar stretchingul dinamic este folosit din ce în ce mai mult în încălzire și în competiții. Există probe că poate exista o scădere a forței ca urmare a unor perioade lungi de stretching static. Obiective. Scopul lucrării este de a determina diferențele de putere în săritură înainte și după stretchingul dinamic la sportivi tineri. Materiale și metode. Participanții au fost sportivi tineri (N=18), cu vârstele între 14 și 16 ani care au fost măsurați cu covorul MGM-15. Rezultate. S-a constatat o diferență statistică semnificativă în scorurile între cele două situații experimentale fapt ce ne face sa constatăm că stretchingul dinamic are efect. Concluzii. Rezultatele au arătat ca puterea a fost semnificativ mai mare după stretchingul dinamic. Mai mult stretchingul dinamic ar trebui sa fie utilizat pentru creșterea puterii în sărituri. Cuvinte cheie: stretching dinamic, putere, sportivi băieţi, sărituri.